Effect of CO Molecule Orientation on the Reduction of Cu-Based Nanoparticles - Sergey Y. Sarvadii; Andrey K. Gatin; Vasiliy A. Kharitonov; Nadezhda V. Dokhlikova; Sergey A. Ozerin; Maxim V. Grishin; Boris R. Shub (Nanomaterials, 2021)
The adsorption of CO on the surface of Cu-based nanoparticles was studied in the presence of an external electric field by means of scanning tunneling microscopy (STM) and spectroscopy (STS). Nanoparticles were synthesized on the surface of a graphite support by the impregnation–precipitation method. The chemical composition of the surface of the nanoparticles was determined as a mixture of Cu2O, Cu4O3 and CuO oxides. CO was adsorbed from the gas phase onto the surface of the nanoparticles. During the adsorption process, the potential differences ΔV = +1 or −1 V were applied to the vacuum gap between the sample and the grounded tip. Thus, the system of the STM tip and sample surface formed an asymmetric capacitor, inside which an inhomogeneous electric field existed. The CO adsorption process is accompanied by the partial reduction of nanoparticles. Due to the orientation of the CO molecule in the electric field, the reduction was weak in the case of a positive potential difference, while in the case of a negative potential difference, the reduction rate increased significantly. The ability to control the adsorption process of CO by means of an external electric field was demonstrated. The size of the nanoparticle was shown to be the key factor affecting the adsorption process, and particularly, the strength of the local electric field close to the nanoparticle surface.